Efficacy of Second Forward-View Colonoscopy to Improve Adenoma Detection of Right-Side Colon: Systematic Review and Meta-Analysis - Hyun Jung Kim; Hyuk Yoon; Jung Won Lee (The Korean Journal of Gastroenterology)
Background/Aims: The second forward view (SFV) has been considered an effective method to improve the adenoma detection rate (ADR) in the right-side colon. On the other hand, there is insufficient evidence on how much the ADR is improved compared to standard one forward view (OFV) colonoscopy. A systematic review and meta-analysis were performed to determine the efficacy of improvement in the ADR by SFV colonoscopy. Methods: This study conducted a systematic literature search in Medline, Embase, and Cochrane Library until Sep 2024. Two independent investigators (HJK, JWL) conducted a database search, and studies regarding the SFV or retroflexion were selected. The primary outcomes were the ADR of the right-side colon, polyp detection rate, and withdrawal time. Statistical analyses were performed using STATA 18.0 Special edition. Results: Ten studies with 5,886 patients were included in this review. The pooled ADR of SFV colonoscopy for the right colon was significantly higher than that of the OFV, with a risk ratio (RR) of 1.25 (95% CI, 1.13–1.38 I2=0.0%). This result was statistically significant in three non-randomized trials (RR 1.19, 95% CI 1.06–1.34, I2=0.0%) with low heterogeneity. The right-sided polyp detection rate (RR 1.19, 95% CI 1.06–1.34, I2=61.6%) and the ADR of the whole colon (RR 1.10, 95% CI 1.01–1.20, I2=0.0%) were also significantly higher than those of OFV colonoscopy. Conclusions: SFV colonoscopy is an effective method to improve the ADR of the right colon.